Relationship between the Direction of Ophthalmic Artery Blood Flow and Ocular Microcirculation before and after Carotid Artery Stenting - Masashi Ishii; Morito Hayashi; Fumihiko Yagi; Kenichiro Sato; Goji Tomita; Satoshi Iwabuchi (Journal of Ophthalmology)
When internal carotid artery stenosis is accompanied by ocular ischemic syndrome, intervention is recommended to prevent irreversible visual loss. In this study, we used laser speckle flowgraphy to measure the ocular microcirculation in the optic nerve head before and after carotid artery stenting (CAS) of 40 advanced internal carotid stenosis lesions from 37 patients. The aim was to investigate the relationship between ocular microcirculation and the direction of ophthalmic artery blood flow obtained by angiography. We found that there was a significant increase in blood flow after CAS (P=0.003). Peak systolic velocity as an indicator of the rate of stenosis was also significantly higher in the group with retrograde/undetected flow of the ophthalmic artery than in the group with antegrade flow (P=0.002). In all cases where retrograde flow of the ophthalmic artery was observed before stenting, the flow changed to antegrade after stenting. Through the use of laser speckle flowgraphy, this study found that CAS can improve ocular microcirculation. Furthermore, while patients displaying retrograde flow of the ophthalmic artery before stenting have a poor prognosis, CAS corrected the flow to antegrade, suggesting that visual loss can be prevented by improving the ocular microcirculation.